Generic Skills of Malaysian University Students - Md. Yunus, Aida Suraya; Abu, Rosini; Mohd Nor, Sharifah; Ahmad Tarmizi, Rohani; Abu Bakar, Kamariah; Wan Ali, Wan Zah; Hamzah, Ramlah; Ismail, Habsah (National Higher Education Researh Institute, 2005)
Demands at the workplace are transforming the kinds of knowledge, skills, and attitudes needed for successful work performance. Evidence from employer surveys suggested that employers are often more concerned about soft skills or attitudes rather than technical knowledge or competencies (Stasz, Ramsey, Eden, Melamid, & Kaganoff, 1996). Empirical studies on work found that employers and workers also feel skills such as problem solving, communication and the ability to work in teams, are increasingly important for workplace success (Stasz et al., 1996). Therefore, apart from providing students with the technical knowledge, universities are entrusted with the task of grooming students with the generic skills required to be successful workers. The importance of some of these skills are documented in the Quality Assurance in Public Universities of Malaysia: Code of Practice document, which states that the quality of a university programme is assessed by the ability of its graduates in carrying out their expected roles with responsibility in society. As stated in the document, among the competencies that students should demonstrate at the end of the programme are critical thinking, problem solving, creative decision making and ability to communicate, apart from mastery of knowledge in the specific fields (Quality Assurance Division, 2004)